The Position of Village Owned Enterprises (BUMDes) Which Are Incorporated According To Law No. 11 of 2020 Copyright Work - Dira Dinda Alti; Henry Aspan; Onny Medaline (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
Currently, the presence of business entities in Indonesia continues to increase in terms of quantity and form, and some are legal entities or not. Village-Owned Enterprises (BUMDes) are expected to improve the economy and public services to the community in the village. Law Number 6 of 2014 concerning Villages (UU Desa) mentions BUMDes as a business entity. The Business Entity in question is not specifically specified in the Village Law. This study aims to analyze the status of BUMDes as legal subjects and after the enactment of Law Number 11 of 2020 concerning Job Creation (UU Cipta Kerja) and its implications because Article 117 of the Job Creation Law changed article 1 number 6 of the Village Law which previously referred to BUMDes as an agency business is converted into a legal entity.